Optimization of PCR Primers for Detection of Extended-Spectrum Beta-Lactamase Targeting CTX-M and TEM Genes - Kurniati, Dwi Elfira; Riani, Catur; Hardiyanti, Renny; Rachmawati, Dian (School of Life Sciences and Technology, Institut Teknologi Bandung, 2025)
Extended-Spectrum Beta Lactamase (ESBL) is an enzyme that inhibit the activity of third-generation cephalosporin antibiotics. CTX-M and TEM are the genes encoding the ESBLs. The horizontal spread of these gene from one bacteria to another leads to increased bacterial resistance. Molecular-based bacterial identification methods such as Polymer Chain Reaction are methods that are currently used because they provide faster and more specific results. Therefore, in this study, a method for identifying bacteria that produce ESBL was created by targeting CTX-M and TEM genes. In this study, two pairs of primers were designed using in silico method, then the characteristics of the primers were analyzed. The primer annealing temperature was optimized using 55 and 60oC temperatures. The results of the in silico analysis showed that both pairs of primers met the ideal characteristics of a primer, as the Tm, %GC content, and secondary product values fulfilled the required criteria. Meanwhile, the results of the primer annealing temperature optimization indicated that the optimal temperature for the PCR method using both primers was 60°C.